2005
DOI: 10.1158/0008-5472.can-05-0743
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3, A Novel Tumor Suppressor, Is Frequently Inactivated in Gastric Cancer by Protein Mislocalization

Abstract: Loss of RUNX3 expression is suggested to be causally related to gastric cancer as 45% to 60% of gastric cancers do not express RUNX3 mainly due to hypermethylation of the RUNX3 promoter. Here, we examined for other defects in the properties of RUNX3 in gastric cancers that express RUNX3. Ninety-seven gastric cancer tumor specimens and 21 gastric cancer cell lines were examined by immunohistochemistry using novel anti-RUNX3 monoclonal antibodies. In normal gastric mucosa, RUNX3 was expressed most strongly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
252
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(270 citation statements)
references
References 44 publications
14
252
2
2
Order By: Relevance
“…As shown in Figure 3b, bacterial b-galactosidase was detected in gastric epithelial cells of Runx3 þ /À mouse, with high expression at surface epithelial cells and the bottom of the gland where chief cells reside. This expression pattern is reminiscent of those previously shown for human and mouse gastric epithelium by in situ hybridization as well as immunohistochemistry using anti-RUNX3 monoclonal antibody (Li et al, 2002;Ito et al, 2005).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…As shown in Figure 3b, bacterial b-galactosidase was detected in gastric epithelial cells of Runx3 þ /À mouse, with high expression at surface epithelial cells and the bottom of the gland where chief cells reside. This expression pattern is reminiscent of those previously shown for human and mouse gastric epithelium by in situ hybridization as well as immunohistochemistry using anti-RUNX3 monoclonal antibody (Li et al, 2002;Ito et al, 2005).…”
supporting
confidence: 77%
“…R3-1E10 and R3-3F12 yielded immunohistochemical Runx3 expression in gastrointestinal tract epithelium K Ito et al patterns that were quite similar to the expression pattern of b-galactosidase in Runx3 þ /À stomach (Figure 3b). In the case of the chief cells, cytoplasmic Runx3 localization was immunodetected by R3-1E10 and R3-3F12 as we described for human gastric epithelium (Figure 3c; Ito et al, 2005). Significantly, however, neither R3-10C7 nor R3-8C9 reacted with the wild-type gastric epithelial cells (Figure 3a).…”
Section: Runx3 Expression In Gastrointestinal Tract Epithelium K Ito supporting
confidence: 64%
See 1 more Smart Citation
“…RUNX3 is 1 of the 3 Runt-domain transcription factors that function in the TGF-/SMAD signaling pathway, which is essential for developmental and physiological processes 9,10 . We have shown that loss of RUNX3 abrogates TGF- signaling and that RUNX3 is inactivated in more than 80% of gastric cancers, not only by gene silencing but also by protein mislocalization 11,12 . RUNX3 directly up-regulates the cyclin-dependent kinase inhibitor, p21 WAF1/Cip113 and the proapoptotic gene, Bim, 14,15 in response to TGF- signaling and down-regulates VEGF 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell extracts from COS-7 cells expressing exogenous RUNX3; normal skin cell line CRL-7761 (American Type Culture Collection (ATCC), Manassas, VA, USA); BCC-derived cell line CRL-7762 (ATCC); and gastric cancer line SNU5 (ATCC), which overexpresses endogenous RUNX3. Western blot was performed using RUNX3-specific monoclonal antibody R3-5G4, as described by Ito et al (2005). …”
mentioning
confidence: 99%